Pay for percentile - Gadi Barlevy; Derek Neal (Federal Reserve Bank of Chicago, 2009)
We propose an incentive pay scheme for educators that links educator compensation to the ranks of their students within appropriately defined comparison sets, and we show that under certain conditions our scheme induces teachers to allocate socially optimal levels of effort to all students. Because this scheme employs only ordinal information, our scheme allows education authorities to employ completely new assessments at each testing date without ever having to equate various assessment forms. This approach removes incentives for teachers to teach to a particular assessment form and eliminates opportunities to influence reward pay by corrupting the equating process or the scales used to report assessment results. Our system links compensation to the outcomes of properly seeded contests rather than cardinal measures of achievement growth. Thus, education authorities can employ our incentive scheme for educators while employing a separate system for measuring growth in student achievement that involves no stakes for educators. This approach does not create direct incentives for educators to take actions that contaminate the measurement of student progress.
Keywords: 330; Lehrkräfte; Leistungsentgelt; Bildungsniveau; Extensives Spiel; Theorie